The red sky enigma over Svalbard in December 2002: a model using polar stratospheric clouds - N. D. Lloyd; D. A. Degenstein; F. Sigernes; E. J. Llewellyn; D. A. Lorentzen (Annales Geophysicae, 2005)
An anomalous red glow due to scattered sunlight was observed at Longyearbyen (78° N, 15° E) on 6 December 2002 from 07:30UT to 13:30UT when the solar zenith angle varied between 100.7° and 104°. A model for this red sky event using sunlight scattered in a two stage process by Polar Stratospheric Clouds (PSC) at 25km is presented and demonstrated to be feasible. The model requires a significant fraction of the polar vortex, which is cold enough for the formation of ice PSC, to be occupied with PSC with an integrated vertical extinction of approximately 0.037 at 845nm. Given these conditions, the model is able to predict, within an order of magnitude, the spatial distribution of intensities measured by meridional scanning photometers located at Longyearbyen across the visible and near infra-red spectrum. Keywords. Aerosols and particles; Transmission and scattering of radiation; Polar Meteorology